Extrauterine growth restriction in preterm infants: Postnatal growth pattern and physical development outcomes at age 3–6 years - Lan, Siyuan; Fu, Huanhuan; Zhang, Rui; Zhong, Guimei; Pan, Liya; Bei, Fei; Hong, Li (Frontiers in Pediatrics, 2022)
Objectives: To investigate the postnatal growth trajectories of preterm infants and evaluate the association between extrauterine growth restriction (EUGR) at discharge and adverse physical growth outcomes at 3-6 years old. Methods: Premature infants admitted to Shanghai Children's Medical Center within 24 hours after birth from January 1, 2016, to December 31, 2018 were enrolled. Neonatal complications, nutrition support, and anthropometric data were collected and analyzed to diagnose EUGR on different definitions at discharge. Weight and height of each subject were collected by telephone investigation from September 1 to November 31, 2021 to access the incidences of overweight/obesity, short stature, and thinness at 3-6 years old . Results: 527 preterm infants were included in the final sample. The overall mean weight and height Z-scores were -0.37±0.97 SD and -0.29±1.18 SD at birth, and increased to -0.03±1.11 SD and 0.13±1.2 SD at follow-up, respectively. Logistic regression analysis indicated longitudinal EUGR for head circumference as the risk factor of overweight or obesity, cross-sectional EUGR for height as the risk factor of short stature, and delayed EN as the risk factor of thinness. Conclusions: The growth trajectories of preterm newborns tended towards the normal direction. Longitudinal EUGR on head circumference and cross-sectional EUGR on height at discharge were associated with adverse physical growth outcomes at 3-6 years old.